Corporate social responsibility disclosure and financial reporting quality: Evidence from Gulf Cooperation Council countries - Mawih Kareem AL Ani (Borsa Istanbul Review, 2021)
This study examines the effect of corporate social responsibility disclosure (CSRD) on earnings quality (EQ) in member countries of the Gulf Cooperation Council (GCC). Using 1845 firm-year observations covering the 2008–2016 period, this study performs panel data regressions to examine the association between CSRD as measured by a dummy variable and three common EQ measures, namely, value relevance (VR), accrual quality (AQ), and earnings persistence (PER). The study concludes that CSRD in three of the six GCC countries (Bahrain, Saudi Arabia, and the United Arab Emirates) has a positive and significant association with EQ in terms of VR. The use of generalized least squares (GLS) shows that CSRD has an effect on AQ in Kuwait and Bahrain whereas CSRD has an effect on PER only in Kuwait. Regulators of capital markets should use CSR information as guidelines to improve financial reporting quality and achieve better allocation of resources in capital markets.